2014
DOI: 10.1007/s10903-014-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking, Cannabis and Tobacco Use Among Ethnic Norwegian and Ethnic Minority Adolescents in Oslo, Norway

Abstract: The aim of the study was to assess prevalence and factors associated with binge drinking, cannabis use and tobacco use among ethnic Norwegians and ethnic minority adolescents in Oslo. We used data from a school-based cross-sectional survey of adolescents in junior- and senior high schools in Oslo, Norway. The participants were 10,934 adolescents aged 14-17 years, and just over half were females. The sample was comprised of 73.2 % ethnic Norwegian adolescents, 9.8 % 1st generation immigrants, and 17 % 2nd gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 27 publications
15
61
1
Order By: Relevance
“…Cannabis use seems to have low prevalence among Norwegian students compared to cannabis use in some other student populations (Allen & Holder, 2014;Johnston et al, 2011). While the current results support the notion of drug use as a culturally specific phenomenon (Abebe, Hafstad, Brunborg, Kumar, & Lien, 2015), cannabis use among Norwegian students should not be considered marginal, as about one in ten reported use in the past six months.…”
Section: Prevalence Of Cannabis Use Among Norwegian Studentscontrasting
confidence: 64%
“…Cannabis use seems to have low prevalence among Norwegian students compared to cannabis use in some other student populations (Allen & Holder, 2014;Johnston et al, 2011). While the current results support the notion of drug use as a culturally specific phenomenon (Abebe, Hafstad, Brunborg, Kumar, & Lien, 2015), cannabis use among Norwegian students should not be considered marginal, as about one in ten reported use in the past six months.…”
Section: Prevalence Of Cannabis Use Among Norwegian Studentscontrasting
confidence: 64%
“…Tobacco use was found to be at similar levels among immigrants and native-born Norwegians. Interestingly, the study found little evidence of the practices of the host culture being adopted over time, with lower rates of binge drinking and cannabis use remaining for second-generation immigrant youth in Norway (Abebe et al, 2015).…”
Section: Mortality Lower Among Immigrants Than Native Populationsmentioning
confidence: 78%
“…In addition, to our knowledge the prevalence of alcohol use and illicit drug use among Kurdish migrants has not been reported before. According to previous literature, alcohol use among migrants in Europe seems to depend on the region of origin, and alcohol consumption and binge drinking among non-European migrants seems to be lower than in the general population [12][13][14][15][16][17]. The smoking rates of migrant populations in comparison with the general populations in European studies seem to vary according to migrant groups studied, and depend on the region of origin, gender and age of the migrants [12,15,16,18].…”
Section: Introductionmentioning
confidence: 83%
“…According to previous literature, alcohol use among migrants in Europe seems to depend on the region of origin, and alcohol consumption and binge drinking among non-European migrants seems to be lower than in the general population [12][13][14][15][16][17]. The smoking rates of migrant populations in comparison with the general populations in European studies seem to vary according to migrant groups studied, and depend on the region of origin, gender and age of the migrants [12,15,16,18]. The findings of European studies reporting the prevalence of cannabis use among migrant adolescents of non-European origin compared with the general population adolescents are contradictory [12,13,19].…”
Section: Introductionmentioning
confidence: 90%